2007
DOI: 10.1038/oby.2007.294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Exercise on Metabolic Syndrome Improvement in Response to Weight Reduction

Abstract: OKURA, TOMOHIRO, YOSHIO NAKATA, KAZUNORI OHKAWARA, SHIGEHARU NUMAO, YASUTOMI KATAYAMA, TOMOAKI MATSUO, AND KIYOJI TANAKA. Effects of aerobic exercise on metabolic syndrome improvement in response to weight reduction. Obesity. 2007;15:2478 -2484. Objective: The objective was to test effects of aerobic exercise training on metabolic syndrome (MetSyn) improvement in response to weight reduction. Research Methods and Procedures: A total of 459 overweight and obese women (age, 49 Ϯ 9 years; BMI, 28 Ϯ 3 kg/m 2 ) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 25 publications
1
47
0
2
Order By: Relevance
“…It is well known that body weight loss through a direct (supervised) lifestyle intervention (LSI) improves metabolic disorders related to obesity. 9,10 However, it is not known whether an indirect LSI through one family member can affect weight loss and the MetS traits of other, untreated family members. Recently, Christakis and Fowler 11 indicated that obesity can spread in social networks, such as friends, siblings and spouses.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that body weight loss through a direct (supervised) lifestyle intervention (LSI) improves metabolic disorders related to obesity. 9,10 However, it is not known whether an indirect LSI through one family member can affect weight loss and the MetS traits of other, untreated family members. Recently, Christakis and Fowler 11 indicated that obesity can spread in social networks, such as friends, siblings and spouses.…”
Section: Introductionmentioning
confidence: 99%
“…Following the 3-month intervention period, participants showed a moderate weight loss of 8% -13% and improvement in MS factors. Complimenting this work, another study from our laboratory showed that when Japanese women participated in a diet-only or diet plus exercise intervention, the adjusted odds ratio was 1.00 or 3.68 for body weight loss (95%CI, 1.02-17.6) (P = 0.04), respectively 13) . These studies demonstrate that, for obese Japanese adults with MS prevalence, aerobic exercise or physical activity plus diet intervention is more effective than diet alone at reducing body weight and MS associated factors.…”
Section: Exercise and Metabolic Syndromementioning
confidence: 86%
“…Based on a series of weight loss studies conducted in our laboratory 11,13,[43][44][45] , Sasai et al (2008) 44) found a proportionally greater loss in VF following exercise alone when compared to diet alone. More recently, we reported that physical activity (PA) intensities modulate the exercise-induced reduction in intra-abdominal fat 45) .…”
Section: Exercise-and/or Diet-induced Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…The main effect of exercise on insulin resistance is the increased expression of intracellular insulin signaling, particularly in GLUT4 skeletal muscle (TeranGarcia et al, 2005). The uptake by skeletal muscle represents the largest component of glucose disposal (Okura et al, 2007). Most of the uptake of glucose is used in the synthesis of glycogen.…”
Section: Discussionmentioning
confidence: 99%